High-speed and low-power serial accumulator for serial/parallel multiplier - Meher, Manas Ranjan (2010)
This paper presents a new approach to serial/parallel multiplier design by using parallel 1's counters to accumulate the binary partial product bits. The 1's in each column of the partial product matrix due to the serially input operands are accumulated using a serial T-flip flop (TFF) counter. Consequently, the column height is reduced from N to [log2 N]+1. This logarithmic reduction results in a very small carry save adder (CSA) array or tree required before the two final summands are added up to obtain the final product. The counters can be clocked at very high frequency (around 1.5 GHz as dictated mainly by the TFF propagation delay) and the accumulation frequency is independent of the operand size. The proposed accumulation method achieves 33%, 38%, 43% gain in speed respectively for 31, 63, 127 operands accumulators and on average 42% reduction in power consumption over CSA based accumulation implemented in 0.18 µm CMOS technology.